2011
DOI: 10.1029/2010jd015313
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution climate change simulations for the Jordan River area

Abstract: [1] For the estimation of future climate conditions in the Jordan River region, the National Center for Atmospheric Research-Penn State University meteorology model in the versions 3.5 and 3.7 driven with boundary data from the Max-Planck-Institute for Meteorology and Hadley Centre global circulation models and the Special Report on Emission Scenarios A1B emission scenario has been used. The spatial resolution of the nested dynamic downscaling approach was 18.6 km, and the transient runs were performed for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 59 publications
5
67
0
Order By: Relevance
“…Kharin et al (2007) analyzed the weather extremes calculated by the global climate models participating in the IPCC Fourth Assessment Report and concluded that the models simulate present-day warm extremes reasonably well compared to meteorological re-analysis data. Furthermore, the PRECIS results are qualitatively consistent with those of previously published high-resolution climate model studies (Evans 2010;Kitoh et al 2008;Krichak et al 2011;Ö nol and Semazzi 2009;Smiatek et al 2011).…”
Section: Methodssupporting
confidence: 81%
“…Kharin et al (2007) analyzed the weather extremes calculated by the global climate models participating in the IPCC Fourth Assessment Report and concluded that the models simulate present-day warm extremes reasonably well compared to meteorological re-analysis data. Furthermore, the PRECIS results are qualitatively consistent with those of previously published high-resolution climate model studies (Evans 2010;Kitoh et al 2008;Krichak et al 2011;Ö nol and Semazzi 2009;Smiatek et al 2011).…”
Section: Methodssupporting
confidence: 81%
“…However, this also implies high data requirements and a high number of defined terms (Alley, 1984;Paulo and Pereira, 2006). Hence, there is also a need for simpler drought indices, relying on fewer data and fewer calculations (Hayes et al, 1999;Smith et al, 1993). The Australian Bureau of Meteorology favors the drought index deciles where precipitation is ranked from lowest to highest and split into 10 groups (Gibbs and Maher, 1967).…”
Section: T Törnros and L Menzel: Addressing Drought Conditions Undementioning
confidence: 99%
“…The eastern Mediterranean countries face increasing water stress due to enhanced water withdrawal as well as higher annual mean temperatures and decreased annual precipitation from climate change (Milano et al, 2012;Smiatek et al, 2011). In this region, supplementary agricultural irrigation is necessary due to the insufficient precipitation.…”
Section: Introductionmentioning
confidence: 99%